The effect of psychologic Well-Being on Innovative Work Behavior: A study on General Directorates of Zakho Independent Administration - Zeravan Bashar Ahmed; Zeravan Abdulrahman Omar (مجلة الدراسات الاقتصادية والادارية)
This study explores the effect of psychological well-being in promoting innovative work behavior by studying the perspectives of employees working in the general directorates of the Zakho Autonomous Administration in the Kurdistan Region of Iraq. The primary goal was to know the effect of psychological well-being in enhancing creative work behavior within the specific context of the administrative environment. The study was conducted in general directorates using a descriptive and analytical methodology. The questionnaire was used as the primary tool for collecting data. Data analysis was performed using both SPSS v26 and Smart PLS v 4.1.0.9 (82) correct answers were collected from a total of 105 distributed questionnaires. The results found that there is a strong and statistically significant positive relationship between psychological well-being and innovative work behavior. Psychological well-being plays a pivotal role in enhancing the effectiveness of administrative structures in order to provide a suitable environment that allows employees to be creative and develop their work in order to better serve customers. While these findings are compelling in the context of the study, caution is necessary when generalizing them to other administrative settings. Further research is recommended to delve into the nuances of psychological well-being across diverse contexts. This study contributes valuable insights for organizational leaders seeking to improve performance through psychological well-being. By understanding and benefiting from the factors that lead to psychological well-being, organizations can promote better results and achieve creative behavior.